Types of Renal Stones and its Variation with Age and Gender in a University Hospital of Nepal - Joshi, H.N.; Singh, A.K.; Karmacharya, R.M. (Kathmandu University Medical Journal, 2020)
Background Types of renal stones have profoundly changed in the last half-century, parallel to the change in lifestyle and dietary habit, with an increase of calcium stones. Among many lithogenic factors age and gender are considered to be associated with the types of renal stones. Studies evaluating the influence of age and gender on the distribution of the types of urinary calculi are scarce in Nepal. Objective To explore the influence of age and gender on different types of urolithiasis. Method This is a single center prospective study encompassing urolithiasis during a study period of 18 months. All the stone retrieved from the patients after surgery were sent for biochemical analysis of the stone. The result was then compared with the age and gender of the study population. Result Calculi from a total of 107 patients were analyzed (62 from males and 45 from females). Mixed stones consisting of calcium oxalate and calcium phosphate were the predominant constituent in 74.16% of stones, followed by uric acid, struvite and cystine stones. We found predominance of Calcium stones in males (47.66%) vs 36.44% in females and predominance of struvite stones in females (7.47%) vs 3.73% in males. Age group of 21-40 years has the main burden of stone. Conclusion Being aware and having better knowledge of risk factors, composition and correlation with age and gender can provide personalized guidance to prevention and avoid recurrence of urolithiasis.